2016
DOI: 10.7717/peerj.1593
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing ecosystem functions of the active microbial community of the Baltic Sea oxygen depleted sediments

Abstract: Baltic Sea deep water and sediments hold one of the largest anthropogenically induced hypoxic areas in the world. High nutrient input and low water exchange result in eutrophication and oxygen depletion below the halocline. As a consequence at Landsort Deep, the deepest point of the Baltic Sea, anoxia in the sediments has been a persistent condition over the past decades. Given that microbial communities are drivers of essential ecosystem functions we investigated the microbial community metabolisms and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 79 publications
(111 reference statements)
0
31
0
1
Order By: Relevance
“…This supposition is corroborated by the reported identification of very low amount of mRNA in dormant laboratory cultures of Mycobacterium tuberculosis 39 , and revelation of strong positive correlation between the abundance of bacterial mRNAs involved in cell division and in situ concentration of bacterial cells cell, during the metatranscriptomic exploration of anaerobic Peru Margin sediments 40 . Notably, metatranscriptome analysis has also been used to delineate active prokaryotic community functions in O 2 -depleted sediments of Baltic Sea that are biogeochemically comparable with the ASOMZ sediments 41 .…”
Section: Discussionmentioning
confidence: 99%
“…This supposition is corroborated by the reported identification of very low amount of mRNA in dormant laboratory cultures of Mycobacterium tuberculosis 39 , and revelation of strong positive correlation between the abundance of bacterial mRNAs involved in cell division and in situ concentration of bacterial cells cell, during the metatranscriptomic exploration of anaerobic Peru Margin sediments 40 . Notably, metatranscriptome analysis has also been used to delineate active prokaryotic community functions in O 2 -depleted sediments of Baltic Sea that are biogeochemically comparable with the ASOMZ sediments 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis revealed the presence of diverse methanogen communities distributed along the different geochemical zonations, including those from known TMA‐utilizers, for example, Methanococcoides and Methanosarcina (Zhuang et al ., ). Similarly, metatranscriptomic data from anoxic sediment in the Baltic Sea revealed that mcrA transcripts affiliated to Methanosarcina were highly abundant, suggesting a role of TMA‐dependent methanogenesis in the sediment (Thureborn et al ., ).…”
Section: Tma‐dependent Methanogenesismentioning
confidence: 97%
“…Interestingly, the relative abundance of such OTU decreases in shallower sediments, where other phylotypes occupy higher proportions of the cyanobacterial sequences pool. The presence and activity of Cyanobacteria in marine and lacustrine sediments at depths far higher than 3 m, where the penetration of solar radiation is limited, has been widely reported in literature [62][63][64][65]. Moreover, several studies described how microalgal and cyanobacterial community structure and diversity in freshwater lake sediments vary in relation to water depth, often as a consequence of disturbance events affecting shallow sediments, i.e.…”
Section: Trends In Geochemistry and Microbial Community Structurementioning
confidence: 99%